Quão romance é minha vida amorosa! : namoro virtual e narrativas - Silva, Vergas Vitória Andrade da (2012)
This research aims to acknowledge the virtual dating phenomenon. The research deals with this phenomenon in Orkut, a social networking website. Thus, it considers debates and forums that were present in a Brazilian Orkut online community called Conheci meu amor pela internet (I met my love through the Internet). As a staring point the research dealt with issues such as: what are the debates about? How can we deal with practices that question their own dating process? According to the initial hypothesis, these debates reveal different contemporary social aspects: 1) they emerge as a response to demands on behalf of a society that is rather reflexive. This reflexive element is fundamental for the constitution of the self 2) these debates work as support elements in social relations that are built upon this sphere. In this context, individuals write about themselves and constitute themselves as real individuals that acquire a sense as subjects; and 3) people discuss online dating as form reconstructing former experiences. Empirical analysis demonstrates that these forums and polls present themselves as a social phenomenon that allows a particular form of self presentation on the internet. In order for these subjects to present themselves they built their own self narratives. What is possible to acknowledge considering these narratives is that there is a predominance of the element of intrigue that is further solved and demonstrate a satisfactory result. These narrators then choose online dating situation that present happy endings and happiness that are associated to romantic ideals that are worthwhile being shown. The contents present in these narratives are dealt with by the research. Thus, this work defends the thesis that the online dating narratives are a mixture of facts and fiction once all experiences deal with romantic imaginary as well as personal dating experience. Thus, the research is an attempt to understand what goes on the forums and debates that deal with the fictionalized and dramatized daily experiences in the performances that are similar to games. This is possible due to the fact that there is use of romantic fables and concrete experiences realized by online dating